Pengembangan Booklet Berbasis Aplikasi Canva Pada Siswa SMP Materi Gerak Dan Gaya - Asra, Azmi; Syahropi, Hamid; Junaidi, Nurhikmah Sasna; Daruwati, Ika; Hatika, Rindi Genesa (JURNAL PENDIDIKAN ROKANIA, 2024)
This research aims to describe innovative and creative learning media in the form of booklets using the Canva application in natural science learning about movement and force. This research was carried out at SMP Negeri 1 Rambah Hilir April-September 2024. This research used the Research and Development (R&D) development model with the ADDIE design, the stages involved included, (1) analysis, (2) design, (3) development, (4) Implementation and (5) evaluation. However, this research only reached the implementation stage, namely the product revision stage after small group trials. The research population and sample were all 22 class VII students of SMP Negeri 1 Rambah Hilir, Rambah Hilir District. The research sampling technique used was total sampling. Data were collected using non-tests in the form of questionnaires and data were analyzed descriptively. The results of the research show that the development of a science booklet on motion and force as a whole is included in the "very feasible" category with an average percentage of 84.5%. Based on the validation of language experts with a percentage of 91.7%, it is included in the "very feasible" category, the validation of material experts with an average percentage of 69% is included in the "decent" category, and the validation of media experts with a percentage of 88.5% is included in the "very appropriate" category. . Meanwhile, for small group trials, the average percentage of 84.3% is included in the "very feasible" category, and field trials have an average percentage of 85.5%, which is included in the "very feasible" category.